The Gospel's Seeds in Massuru Culture: Examining the Teachings of Jesus in Matthew 5:23–24 in the Context of Torajan Culture - Linggi', Lius Bongga; Surbakti, Pelita Hati (KAMASEAN: Jurnal Teologi Kristen, 2024)
Awareness of the unfair treatment of local cultural contexts in the Christian mission movement during the colonial era is increasing in many communities. This is influenced by the church's increasing awareness of the richness of local culture itself. The Gereja Toraja is also part of that reality. For this reason, the Gereja Toraja has made various breakthroughs to give more place to local culture in carrying out the mission of the church. A number of activities and documents produced clearly show the face of The Gereja Toraja with a more friendly paradigm to local culture. However, this excellent breakthrough still needs to be shifted to the realm of practice and concreteness. This is because the paradigm in question is still dominated by theoretical matters. Through this paper, the author raises Massuru's culture as a case study. Through the efforts of contextual theology with an anthropological model, the author found that in the Massuru's culture, the gospel value contained in Matthew 5:23–24 is reconciliation before performing religious rites. Based on this result, the effort to shift the new paradigm in a more concrete direction within the Gereja Toraja will be more interesting and passionate. In turn, Torajan Christians will hopefully be more encouraged to put the message of the Bible into practice and enjoy their faith within the framework of their own culture.